To evaluate the expression, we substitute the given values of j, k, and l into the expression:
```
6k - j^2 + 2k / l
```
Let's calculate the values step by step.
First, we substitute j = 5, k = 12, and l = 3:
```
6(12) - (5)^2 + 2(12) / 3
```
Next, we simplify the expression within parentheses:
```
72 - 25 + 24 / 3
```
Then, we perform the multiplication and division operations:
```
72 - 25 + 8
```
Finally, we combine like terms:
```
55 + 8 = 63
```
Therefore, when j = 5, k = 12, and l = 3, the expression evaluates to 63.
evaluate 6k - j to the power of 2 + 2k divided by l when j=5, k=12 and l=3
1 answer